In Vitro Antimicrobial Activities of Crude Extracts of Two Traditionally Used Ethiopian Medicinal Plants against Some Bacterial and Fungal Test Pathogens - Habtom, Selam; Gebrehiwot, Sibhatu (The International Journal of Biotechnology, 2019)
The aim of the present study was to assess the antimicrobial activities of crude extracts of Solanum incanum and Datura stramonium L. against four bacterial disease-causing species namely; Staphylococcus aureus, Streptococcus agalactiae, Salmonella typhi, Escherichia coli) and two fungal pathogenic species (Aspergillus flavus and Aspergillus niger). Crude extracts of roots of S. incanum and leaves of D. stramonium L. were prepared using absolute ethanol, methanol (99.8%) and distilled water. The potential efficacy resulting extracts were assessed by determining zone of inhibitions on cultures of six selected pathogens by applying disc diffusion method. The minimum inhibitory concentration (MIC) of the plant extracts against the same pathogens was determined using the broth dilution method. Chloroamphenicol and Tilt were used as positive controls for bacterial and fungal pathogens, respectively, while Dimethyl Sulfoxide was used as a negative control for both. The results showed that all the methanolic and ethanolic crude extracts, with the exception of the methanolic crude extract of D. stramonium, had the highest growth inhibitory effects as compared with the water crude extracts on all bacterial pathogens. The methanol crude extract of S. incanum had highest zone of inhibition (22±1.15 mm) against S. agalactiae with a minimum inhibitory concentration of 25mg/ml. Similarly, the methanol crude extract of S. incanum had shown significant antifungal activity against A. niger with inhibition zone of 25.13±0.4mm and a minimum inhibitory concentration of 125mg/ml. The results of the present study indicate the potential of these medicinal plants in treating some bacterial and fungal infection.